Role of the Nrf2-ARE Pathway in Liver Diseases. (9th May 2013) - Shin, Sang Mi; Yang, Ji Hye; Ki, Sung Hwan
Abstract : The liver is a central organ that performs a wide range of functions such as detoxification and metabolic homeostasis. Since it is a metabolically active organ, liver is particularly susceptible to oxidative stress. It is well documented that liver diseases including hepatitis, fibrosis, cirrhosis, and hepatocellular carcinoma are highly associated with antioxidant capacity. NF-E2-related factor-2 (Nrf2) is an essential transcription factor that regulates an array of detoxifying and antioxidant defense genes expression in the liver. It is activated in response to electrophiles and induces its target genes by binding to the antioxidant response element (ARE). Therefore, the roles of the Nrf2-ARE pathway in liver diseases have been extensively investigated. Studies from several animal models suggest that the Nrf2-ARE pathway collectively exhibits diverse biological functions against viral hepatitis, alcoholic and nonalcoholic liver disease, fibrosis, and cancer via target gene expression. In this review, we will discuss the role of the Nrf2-ARE pathway in liver pathophysiology and the potential application of Nrf2 as a therapeutic target to prevent and treat liver diseases.